2010
DOI: 10.1103/physrevb.81.195309
|View full text |Cite
|
Sign up to set email alerts
|

Angular-dependent oscillations of the magnetoresistance inBi2Se3due to the three-dimensional bulk Fermi surface

Abstract: We observed pronounced angular-dependent magnetoresistance (MR) oscillations in a high-quality Bi2Se3 single crystal with the carrier density of 5×10 18 cm −3 , which is a topological insulator with residual bulk carriers. We show that the observed angular-dependent oscillations can be well simulated by using the parameters obtained from the Shubnikov-de Haas oscillations, which clarifies that the oscillations are solely due to the bulk Fermi surface. By completely elucidating the bulk oscillations, this resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
212
6
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(245 citation statements)
references
References 43 publications
(54 reference statements)
25
212
6
2
Order By: Relevance
“…Checkelsky et al 75 performed transport experiments on Ca-doped samples noting an increase in the resistivity, but concluded that surface state conduction alone could not be responsible for the smallness of the resistivities observed at low temperature. Eto et al 76 79 reported signatures of ambipolar transport analogous to graphene. However, in this work also, two contributions to transport were found, the bulk contribution was subtracted so as to obtain the surface contribution, and the surface effect was observed only for top gate voltage sweeps, not back gate sweeps.…”
Section: Introductionmentioning
confidence: 99%
“…Checkelsky et al 75 performed transport experiments on Ca-doped samples noting an increase in the resistivity, but concluded that surface state conduction alone could not be responsible for the smallness of the resistivities observed at low temperature. Eto et al 76 79 reported signatures of ambipolar transport analogous to graphene. However, in this work also, two contributions to transport were found, the bulk contribution was subtracted so as to obtain the surface contribution, and the surface effect was observed only for top gate voltage sweeps, not back gate sweeps.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, no surface-isolated conduction has been observed for this binary compound even with the low carrier density realized by the hole doping. [24][25][26] One of the reasons for the dominant bulk conductance might be ascribed to its band structure, where the Dirac point of the topological surface state is located at or below the bulk valence-band maximum. Actually, the surface-to-bulk scattering has been directly observed by scanning tunneling microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…However, bulk conduction can interfere with the surface transport if the Fermi energy is not well positioned in the gap of the bulk excitation spectrum. [8][9][10][11] Therefore, various attempts have been made to control the Fermi energy and reduce the bulk carrier number and conductivity resulting in a semiconducting (insulating) temperature dependence of the resistivity from bulk electronic states and extending the study of binary bismuth chalcogenides to the ternary compound, Bi 2 Te 2 Se. [12][13][14] The controlled removal of excess electrons was achieved by Sn doping and Bi excess in Bi 2 Te 2 Se.…”
mentioning
confidence: 99%